2014
DOI: 10.1177/1932296814522739
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Glycemic Variability Between Normoglycemic and Prediabetic Subjects

Abstract: So far the criteria for NGT and abnormal glucose tolerance (AGT) are based on HbA1c and 75 g oGTT. We present data on GV and diurnal profiles in stratified cohorts with AGT versus controls. 28 NGT, 42 AGT (15 IGT, 11 IFG, 16 CGI) matched for age and BMI classified by 75 g oGTT underwent a CGM with test meal (TM). Diurnal profiles, glucose excursion after TM, and GV (SD, MAGE) were calculated for day 2 and 3. HbA1c, with its values of 5.5 ± 0.37% versus 5.65 ± 0.36%, was within normal range. Average interstitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 17 publications
8
25
1
Order By: Relevance
“…All of the participants were included with normal fasting glycemia and normal HbA1c values, however, we could observe that some participants were undergoing excursions into glucose intolerant and/or diabetes range during the 48-h CGM. These results confirm previous observations that dysglycemia may be underestimated by traditional methods such as fasting glycemia and HbA1c, and that CGM could serve as a better tool to detect early alterations [ 23 , 24 , 25 ]. Likewise, this study also confirmed altered glucose management in obese subjects with normoglycemia and normal HbA1c.…”
Section: Resultssupporting
confidence: 90%
“…All of the participants were included with normal fasting glycemia and normal HbA1c values, however, we could observe that some participants were undergoing excursions into glucose intolerant and/or diabetes range during the 48-h CGM. These results confirm previous observations that dysglycemia may be underestimated by traditional methods such as fasting glycemia and HbA1c, and that CGM could serve as a better tool to detect early alterations [ 23 , 24 , 25 ]. Likewise, this study also confirmed altered glucose management in obese subjects with normoglycemia and normal HbA1c.…”
Section: Resultssupporting
confidence: 90%
“…Thus, in contrast with previous studies, we examined the influence of glycemic variability among those with diabetes and those without diabetes. The exploration of the latter group was based on prior mechanistic studies suggesting the possible deleterious effect of glycemic variability among individuals without diabetes (17)(18)(19)da suggestion confirmed by our findings. Furthermore, a positive association between VVV of HbA 1c and all-cause mortality has been described among individuals without diabetes in a prior study (20).…”
Section: Discussionsupporting
confidence: 77%
“…This could explain why SD in this cohort, reported to be 1.5, is larger compared to SD reported in other studies in subjects with normal glucose tolerance (ranged 0.5 -0.9). However, other GV measures were similar to those reported from analysis of other datasets (28,31,(41)(42)(43). The accuracy of the CGM systems used in the study, particularly in the hypoglycemic range, is a further limitation and may affect GV measurements.…”
Section: Discussionsupporting
confidence: 76%